Adenosine Kinase Inhibition Augments Conducted Vasodilation and Prevents Left Ventricle Diastolic Dysfunction in Heart Failure With Preserved Ejection Fraction. (August 2019) - Davila, Alec; Tian, Yanna; Czikora, Istvan; Li, Jie; Su, Huabo; Huo, Yuqing; Patel, Vijay; Robinson, Vincent; Kapuku, Gaston; Weintraub, Neal; Bagi, Zsolt
Abstract : Background: Heart failure with preserved ejection fraction (HFpEF) is often manifested as impaired cardiovascular reserve. We sought to determine if conducted vasodilation, which coordinates microvascular resistance longitudinally to match tissue metabolic demand, becomes compromised in HFpEF. We hypothesized that the metabolic vasodilator adenosine facilitates and that inhibition of ADK (adenosine kinase) augments conducted vasodilation for a more efficient myocardial perfusion and improved left ventricle (LV) diastolic function in HFpEF. Methods and Results: We assessed conducted vasodilation in obese ZSF1 rats that develop LV diastolic dysfunction and is used to model human HFpEF. Additionally, conducted vasodilation was measured in arterioles isolated from the right atrial appendages of patients with HFpEF. We found a markedly reduced conducted vasodilation both in obese ZSF1 rats and in patients with HFpEF. Impaired conducted vasodilation was accompanied by increased vascular ADK expression. Isolated rat and human arterioles incubated with adenosine (10 nmol/L) or ADK inhibitor ABT-702 (0.1 µmol/L) both displayed augmented conducted vasodilation. Treatment of obese ZSF1 rats with ABT-702 (1.5 mg/kg, IP for 8 weeks) prevented LV diastolic dysfunction, and in a crossover design augmented conducted vasodilation and improved LV diastolic function. ABT-702 treated obese ZSF1 rats exhibited reduced expression of myocardial carbonic anhydrase 9 and collagen, surrogate markers of myocardial hypoxia. Conclusions: Upregulation of vascular ADK mitigates adenosine-facilitated conducted vasodilation in obese ZSF1 rats and in patients with HFpEF. We propose that pharmacological inhibition of ADK could be beneficial for therapeutic augmentation of conducted vasodilation, thereby improving tissue perfusion and LV diastolic function in HFpEF. Abstract : Supplemental Digital Content is available in the text.